Stock market reaction to animal disease outbreaks: an event study in Korean foot-and-mouth disease - Cho, Chulgu, author; Pendell, Dustin L., advisor; Koontz, Stephen R., committee member; Pritchett, James G., committee member; Hine, Susan E., committee member (Colorado State University. Libraries, 2012)
In Korea, there were five foot-and-mouth disease (FMD) outbreaks between 2000 and 2010. This study examines the impact of the FMD outbreaks on the stock market value of agribusiness firms in Korea using an event study methodology. Eighteen companies in six different groups (i.e., pork, poultry, seafood, imported meat, feed and vaccine) are analyzed. For each outbreak, single-day abnormal returns and multiple-day cumulative abnormal returns are calculated to test for the existence and magnitude of stock price reactions. In addition, changes in volatility after the outbreaks are computed to examine whether the riskiness of returns change due to the events. The results suggest that the FMD outbreaks caused the stock market to react in both a negative and positive manner to related firms. The 2000 outbreaks had the most distinguishing and consenting results to prior expectations. The 2002 results showed relatively stable changes of returns due to appropriate governmental programs. In the 2010 events, some companies' stock market reactions were unexpected and did not meet our prior expectations as a result of other factors such as market supply and demand conditions and another animal disease. The results also suggest that the stock market reactions were more gradual than instantaneous to the FMD outbreaks. This study observed more meaningful values of multi-day cumulative abnormal returns than single-day abnormal returns and understands that these long-lasting impacts are due to the continuous negative news reaching the stock market as there were multiple confirmed cases in all outbreaks. When an outbreak severely impacted a particular business sector, the accumulations of abnormal returns became substantial. Many companies had significant results that met prior expectations, but some groups did not maintain consistency in their reactions to the events. The pork companies realized a negative reaction in the 2000 and the third 2010 events when the outbreak presented a negative outlook for the swine and pork businesses. The poultry and seafood firms reacted positively when there were no other substantial market threats. The imported meat group showed mixed reactions while the vaccine companies had consistent positive reactions that met prior expectations. The feed companies reacted negatively when the outbreaks substantially damaged the livestock production sites. Volatility of the stock prices after the FMD events increased, with more companies showing significant results in a longer-lasting outbreak. The results imply that managers and shareholders of the affected firms should pay more attention on management of their assets when there is an FMD and other animal disease outbreaks. It also implies that appropriate governmental interventions help mitigate damages on the stock market.
Keywords: event study; stock market reaction; FMD; Korea